ANALYSIS OF THE TRANSFORMATION OF STUDENTS CONSUMPTIVE BEHAVIOR THROUGHT E-COMMERCE - Rukmana, Devi Hardianti; Hasanah, Hikmatul; Sofa, Ainur Rofiq (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This research investigates the influence of e-commerce on students’ consumptive behavior at the Faculty of Islamic Economics and Business, Universitas Islam Negeri Kiai Haji Achmad Shiddiq Jember. Using a quantitative approach, data were obtained from 20 students across different study programs through random sampling and analyzed with statistical tests, including validity, normality, linearity, regression, and hypothesis testing. The results demonstrate that e-commerce has a significant and positive effect on consumptive behavior, as shown by the regression analysis (p = 0.016 < 0.05). Students tend to engage in impulsive buying driven by discounts, promotional offers, and lifestyle trends rather than actual needs. These findings highlight the role of e-commerce in shaping consumer lifestyles among students. The study suggests that students develop awareness and self-control strategies to reduce excessive consumption and prioritize essential needs over desires in online shopping activities.